Moving Beyond Bricks and Mortar: Changing the Conversation on Online Education - Teresa Miller; Michael Ribble (Educational Considerations, 2010)
Online learning has changed education in many ways. This change was not mandated, but instead filled a need expressed by students. Picciano and Seaman (2009) estimated that more than a million K-12 students took an online class in 2007-2008.
Keywords: K-12 schools; Bricks and Mortar; teacher; preparation; programs; classroom; higher education; online learning; students